The Relationship between Salivary Sialic Acid Levels and Oral Health in Iraqi Pediatric Population - Thanoon, Raghad Tahseen (American Journal of Biomedicine and Pharmacy, 2025)
Salivary sialic acid levels have been identified as potential biomarkers for assessing oral health, particularly in pediatric populations. In the Iraqi pediatric population, studies suggest that higher levels of sialic acid in saliva are often associated with various oral health conditions, including dental caries and periodontal disease. This study investigates the diagnostic potential of salivary sialic acid and its association with oral health parameters in children aged 5–15 years. Salivary samples from 100 healthy participants were collected and analyzed using spectrophotometric and ELISA techniques. The study employed statistical methods, including ANOVA, Student’s T-test, linear correlation, and multiple regression, with a significance level set at p < 0.05.